EFEKTIFITAS TERAPI HIPNOSIS LIMA JARI TERHADAP PENURUNAN CEMAS PADA ASUHAN KEPERAWATAN PASIEN HIPERTENSI YANG DIRAWAT DI RUANG ARIMBI RST WIJAYAKUSUMA PURWOKERTO - Puska Andriana; Indri Heri Susanti (JURNAL PENGABDIAN MANDIRI, 2022)
Introduction : From the results of observations and interviews conducted by researchers in the Arimbi Room of RST Wijayakusuma Purwokerto, patients generally said they felt anxious about the conditions they experienced, the unfamiliar environment, the uncertainty of the disease and also treatment. The results of a preliminary study in the Arimbi room of RST Wijayakusuma Purwokerto said that patients who entered the hospital experienced a mild level of anxiety 16.7%, moderate anxiety 50% and severe anxiety 33.3%. Purpose: Writing this final scientific paper for nurses is to analyze cases managed in hypertension patients with five finger hypnosis intervention to reduce anxiety in the room in Arimbi. Methods: This type of scientific paper is written with a descriptive case study design by managing one hypertensive patient with anxiety. Result : This KIAN shows that 5 finger hypnosis has proven to be effective in reducing anxiety in hypertensive patients after 1 x 8 hours of action. Conclusion: The 5 finger hypnosis innovation intervention, can be proven effective in reducing the client's anxiety scale, namely by decreasing the HRS-A score in Ny.Y hypertensive patients who experience anxiety after the intervention. Suggestion: it is suggested to: Hospital Institutions, Educational Institutions, Implementing Nurses and Research Nurses to use this 5 finger hypnosis therapy as an alternative to innovative therapy in managing patient anxiety.